Pierre Damien et l’illusion de la conversation épistolaire - Patrick Henriet (L'Atelier du CRH)
This paper presents the correspondence of Peter Damian (180 letters), which is the most important part of his work. Peter Damian is perfectly aware that he practices an intermediate genre between the letter and the edifying treatise. To illustrate this dimension of his correspondence, we examine the relationship between letters and exempla on the one hand, and between letters and preaching on the other. We also emphasize, with examples, the very strong intertextual dimension of this corpus and we return to a striking and, in our opinion, very accurate formula of Owen J. Blum: Peter Damian’s correspondence is a “summa in epistolary form”, since all subjects are dealt with. However, rather than a desire to decipher the world, we are dealing with a project to reform Christian society.In short, Peter Damian’s immense correspondence is an early and unparalleled example of the circulation of a silent word that aims to lay the foundations of a Christian society renovated from the hermitage. This speech hardly calls for reciprocity: it is more the expression of a magisterium than of an exchange